REPUTATION MARKETING THE INTERNET: THEORETICAL ASPECTS - Karpii , O.P.; Mykhailyk , N.I. (The actual problems of regional economy development, 2021)
The article substantiates the theoretical aspects of reputation marketing on the Internet. The purpose of this article is to study the theoretical aspects of the development of reputable marketing on the Internet. In the process of writing the article, inductive deductive methods were used, which were used to form the main stages of identifying the level of reputation on the Internet. Methods of economic analysis and comparison were used in developing a strategy for working on the company's reputation on the Internet. The graphical method is used to clearly display the stages of strategy construction and the formation of a basic platform for improving the reputation of Internet networks. An abstract-logical method is used for theoretical generalizations and formation of conclusions. An overview of reputation detection on the Internet is offered: searching for companies through Google, searching for companies through a social network, searching for companies about a company. It has been found that online reviews play an important part in making a purchase decision. It is substantiated that positive feedback from consumers / customers can solve two tasks together: provide a positive brand image; developing relationships with existing customers, increasing their loyalty and turning ordinary consumers into admirers of the brand. The process of developing a strategy to increase the company's reputation on the Internet is proposed, which includes the following main stages: reputation analysis; goal setting; strategy development; monitoring and analytics. It is justified that the state of reputation on the Internet affects the productivity and effectiveness of the organization, as well as focuses on changing what target audience sees the website. To increase the reputation in the network, the authors proposed to use a basic platform to increase the reputation of the Internet. The main directions of improving the reputation of the Internet are proposed: monitoring of the information field around the brand; CROWD marketing; press releases and publications in the media; content marketing; control of reviews on the site. It has been proven that improving the reputation on the Internet is an important aspect of any business on the Internet and part of an effective marketing strategy.